A case of erythema elevatum diutinum with a monoclonal IgA kappa gammopathy - KAKINOKI Sugako; SASAKI Fumiko; ODAKA Tatsuo; FUTAMURA Syozo (Skin research, 1988)
A 38-year-old man with typical skin lesions symmetrically on the extremities and buttocks for about 10 years and responding well to DDS is presented. His blood examination revealed a monoclonal IgA kappa gammopathy. No sign of multiple myeloma was found by X-ray and scintigram examination of bones and bone marrow examination of the sternum.Review of the recent Japanese literature showed that among 21 reported cases 13 had abnormalities of blood serum, 10 of these having hyper IgA proteinemia. 38歳, 男性。10年来典型的な皮疹 (組織も典型的) を四肢, 磐部に対側性にくり返し, DDSによく反応し, 血清検査でIgA-K型M蛋白血症を伴う症例を経験したので報告した。骨レ線, シンチ像, 胸骨骨髄穿刺で骨髄腫を疑う所見を認めなかった。近年の本邦報告例21例を文献的に考察し, 血清蛋白異常を示すもの13例の中でIgA高値を示す例は10例であった。